Inquiry to the Use of ASEAN Way: China Increase Posturing and Indonesia’s Role in South China Sea Dispute - KOMARUDIN, UJANG; PRAMUJI, PITUT (Universitas Muhammadiyah Yogyakarta, 2018)
As tension in South China Sea has been risen, pundits and scholars quickly forgot how manageable it was once during the period after the Asian Financial Crisis until before Global Economic Crisis of 2008. This paper will focus to identify and elaborate the cause for South China Sea to re-escalate after a decade of sustain peace, while trying to assess the effectiveness of ASEAN Way in defusing the conflict, and understand the role of Indonesia in South China Sea territorial dispute. Findings of the study explained what motivates China to take tougher stance in this matter, first is the internationalization of South China Sea dispute with the submission through International Court of Justice by Malaysia and Vietnam; second the growing international power and influence China gained after the global economic crisis of 2008; third, while China’s growing naval capabilities since a decade ago has made possible for China to extend its power projection far reaching its coastline. Meanwhile Indonesia tried hard to push this agenda in various formal and informal meetings in East Asia, although the noise its making still cannot lured parties involved reluctantly revert back to the old balancing power game.Keywords: South China Sea, ASEAN Way, Indonesia